Legal Protection of Correction Institutional Citizens Who Have Obligation to Work At Rutan Bangli - Luh Putu Pertamawati Armony (Kertha Wicaksana, 2023)
The sentencing process is the estuary of the justice system and law enforcement in Indonesia. However, not many people know that apart from serving time in correctional institutions and detention centers, convicts also undergo a coaching process and undergo mandatory work. Transforming into productive prisons and detention centers so as to generate PNBP and realize a better economy and for WBP itself can provide a decent life and livelihood. The problem of overcapacity, support for development programs in different nomenclature of detention centers and correctional institutions as well as marketing for sustainability and legal protection are obstacles in realizing optimal results from the development program. The problem to be investigated is from the perspective of how prisoners can act as workers, to the process of coaching and legal protection for prisoners who are undergoing compulsory work at the Bangli Class IIB State Detention Center. The research method used is empirical research by taking a statutory, conceptual, case and legal sociology approach, with primary and secondary data sources with research locations at the Rumah Tahanan Negara Kelas IIB Bangli Center. This study uses data collection techniques by interview, observation and documentation as well as recording with interpretation analysis. The results of the research show that prisoners do not only act as objects but are subjects who enthusiastically participate in compulsory work coaching activities for their own development and the rights that should be obtained, the coaching process at the Rumah Tahanan Negara Kelas IIB Bangli Center can run well to fulfill these rights. Prisoners' rights with coaching programs for working with third parties, and legal protection for convicts who are obliged to work are given preventively through applicable laws and regulations and can be conveyed on a reflexive basis to the Correctional Guardian or during the Correctional Observer Team (TPP) session.